Study on Some Integral Inequalities for Pseudo-Integrals - Bayaz Daraby (Sahand Communications in Mathematical Analysis, 2022)
In this paper, we express and prove  Stolarsky, Feng Qi and Markov type inequalities for two classes of pseudo-integrals. One of them concerning the pseudo-integrals based on a function reduces on the g-integral where pseudo-operations are defined by a monotone and continuous function $g$. The other one concerns the pseudo-integrals based on a semiring $( [a, b], \max, \odot )$, where $\odot$ is generated.  The integral  inequalities are  appling in multivariate approximation theory and probability theory and etc.